Design of finned heatsinks having minimum mass - Shilo, G. N.; Ogrenich, E. V.; Gaponenko, N. P. (Видавництво Львівської політехніки, 2010)
The model of heat transfer processes in structural elements of heat sinks with finned surfaces is analyzed; the algorithm of optimizing masses of finned heatsinks is developed.
Keywords: the thermal regime; the finned radiator; construction optimization; iterative algorithm